Human sacrifice, Greece and Rome - Bonnechere, Pierre (The Encyclopedia of Ancient History, 2013)
Human sacrifice is a bone of contention for historians. The concept is elusive: should we distinguish between the victim that is offered to specific gods (human sacrifice) and the one that is not (ritual murder)? This issue very often superimposes modern categories on ancient texts, in which such a distinction is never obvious. Would this distinction remain valid if human sacrifice belonged to representation rather than reality? Comparisons with other cultures remain particularly hazardous if the phenomenon has not been thoroughly studied for each of them.